Tempered fractional version of trapezoid-type inequalities - Hezenci, Fatih; Budak, Hüseyin (Journal of inequalities and applications, 2025)
In this article, trapezoid-type inequalities are proved by means of convex functions according to tempered fractional integral operators. The resulting trapezoid-type inequalities generalize several studies on this subject, including those involving Riemann-Liouville fractional integrals. To obtain these types of inequalities, we utilize the Hölder and power-mean inequalities. Finally, new results are obtained through specific parameter choices.